The thinker: opposing directionality of lighting bias within sculptural artwork - Sedgewick, Jennifer R.; Weiers, Bradley; Stewart, Aaron; Elias, Lorin J. (Frontiers in Human Neuroscience, 2015)
Previous lighting bias research has suggested that individuals tend to perceive the direction of light to come from above and slightly from the left; it has been speculated that this phenomenon is also producing similar lighting preferences within 2-dimensional artwork (e.g., paintings, advertisements). The purpose of the present study was to address if lighting bias was present in the 3-dimensional medium of sculpture by implementing a virtual art gallery lighting paradigm. Thirty-nine participants completed a computer task that consisted of 48 galleries each containing one piece of sculpture (24 sculptures, counterbalanced) which was surrounded by eight lights (above/below, left/right, front/back). Participants would select one light source to illuminate the sculpture in a manner they perceived to be the most aesthetically pleasing. The results indicated a significant preference for lights positioned from above and from the right, a finding that is contradictory to previous lighting bias research examining artwork. An interpretation for the rightward bias applies the perceptual concept of subjective lighting equality. Objects illuminated from the left typically appear brighter in comparison to right-side lighting; in sculpture, however, increased luminosity can reduce the sculptural detail, and may have been compensated via right-side lighting choices within the lighting task.